Notes on the Genus Apotrechus (Orthoptera: Gryllacrididae: Gryllacridinae) from China - Guo, Li-Ying; Shi, Fu-Ming (Zootaxa, 2012)
A key to the species of the genus Apotrechus Brunner von Wattenwyl from China is presented. A new species and a newcombination are reported: A. bilobus sp. nov., A. parvospinus (Liu & Yin, 2002) com. nov. The specimens recorded here are deposited in the Museum of Hebei University.